Analisis Isi Pesan Dakwah Dalam Film Insya Allah Sah Karya Benni Setiawan - Amali, Rijal Nur; Walisyah, Tengku (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This research aims to ascertain the significance of the Islamic ethical message conveyed in the film "Insya Allah Sah" directed by Benni Setiawan, distinguished by both verbal and nonverbal communication. The film is a medium that can be utilized for academic purposes, as the act of spreading religious teachings in this contemporary day is not limited to traditional preaching methods. Movies can benefit viewers, notably by imparting moral lessons encompassing education, culture, and other ethical values. "Insha Allah Sah" is a captivating comedic drama film that warrants investigation due to its exploration of Islamic ethical teachings, particularly about marriage and commitments. The study methodology employed is qualitative research utilizing content analysis techniques. This research methodology pertains to Roland Barthes' semiotic theory, which places emphasis on the examination of the signs present in films, encompassing both linguistic and non-linguistic elements. Data was gathered by firsthand observation of films and examination of conversation, scenes, and symbols depicted in the films. The employed methodology for data analysis is semiotic analysis, which involves the interpretation of each sign present in the film to uncover its underlying meaning. The research findings indicate the presence of many indications of da'wah messages in the film "Insya Allah Sah," encompassing aqidah (religious beliefs), sharia (Islamic law), and morals. The film effectively communicates these concepts through a combination of character speech, visual symbolism, and scenarios that portray Islamic principles. Hence, the movie "Insya Allah Sah" serves as both a source of entertainment and a means of imparting Islamic moral values to its viewers, thereby serving as an impactful platform for preaching in contemporary times.